The Implementation of Jigsaw Methods in Enhancing English Language Comprehension among Health Polytechnic Students - Amelia, Noer; Istanto, Wisnu; Edi-Krause, Sulistyaning; Anggoro, Sapto Dwi; Suemith, Merlissa (CV. Creative Tugu Pena, 2023)
The purpose of this research is to find out how much students at Health Polytechnic benefit from using Jigsaw techniques to better understand written English. In order to effectively communicate and understand medical principles and procedures, having a strong grasp of the English language is crucial in the healthcare industry. The study looked at how well 78 students from Poltekkes Kemenkes Surabaya learned using a Reading Proficiency test, traditional methods, and pre- and post-test experimental designs. It also used T-tests to look at the results. for a subset of the larger topic, which improves the group's ability to solve problems and make informed decisions. When students from different backgrounds have mastered a subject, they get together to share what they've learned and help each other out. The use of a group strategy not only leads to better overall comprehension, but also to the growth of interpersonal and communicative skills. The purpose of this research is to determine if teaching English using the Jigsaw method is effective for students at Health Polytechnics. The study will rely on statistical methods. Keywords: Jigsaw Method, Reading Proficiency, Cooperative Learning Strategy